Taxonomic revision of the Pheidole sikorae species-group (Hymenoptera, Formicidae) from Madagascar - Sebastian Salata (ZooKeys, 2020)
On Madagascar, the ant genus Pheidole Westwood, 1839 is one of the dominant and most diverse ant genera. Modern studies on the diversity of Madagascan Pheidole has been initiated in 2019 and ended a 100 year-long break in studies on this genus from the island. Based on so far published data, there are 69 known Pheidole species on the island divided into sixteen species-groups. It is estimated that 97% of them are endemic. Here we present a revision of the sikorae species group, which appears to be the most species-rich on Madagascar. Forty-four members of this group are recognised and described, and an illustrated identification key to this group is also presented. At present, there are 109 valid species and subspecies of Pheidole known from Madagascar, but this number is expected to increase with upcoming taxonomic revisions of the species groups not revised in this study.